USO DE DIFERENTES ASOCIACIONES VEGETALES POR LAGOMORFOS EN MAPIMÍ, DURANGO, MÉXICO - Arroyo Rodríguez, Víctor (Instituto de Ecología, A.C., 2005)
This study shows that there is a spatial segregation of lagomorphs (Sylvilagus audubonii and Lepus californicus) due to a differential use of vegetation associations in Mapimí (Durango, Mexico), which could contribute to their coexistence in this reserve. Debido principalmente a estrategias